Expertise level influences postural balance control in young gymnasts - Marcolin, G.; Rizzato, A.; Zuanon, J.; Bosco, G.; Paoli, A. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The specificity of postural balance control in sports as gymnastic where complex motor skills are involved is widely debated in the literature. The aim of this study was to investigate in young gymnasts whether the amount of training influenced postural balance control in a simple-task and in a sport-specific task.